Clinical and translational advances in esophageal squamous cell carcinoma - Reichenbach, Zachary Wilmer; Murray, Mary Grace; Saxena, Reshu; Farkas, Daniel; Karassik, Erika G; Klochkova, Alena; Patel, Kishan; Tice, Caitlin; Hall, Timothy M; Gang, Julie; Parkman, Henry P; Ward, Sarah J; et al. (Advances in cancer research, 2019)
Esophageal squamous cell carcinoma (ESCC) is among the most deadly forms of human malignancy characterized by late stage diagnosis, metastasis, therapy resistance and frequent recurrence. Clinical management of ESCC remains challenging and the disease presently lacks approved targeted therapeutics. However, emerging data from recent clinical and translational investigations hold great promise for future progress toward improving patient outcomes in this deadly disease. Here, we review current clinical perspectives in ESCC epidemiology, pathophysiology, and clinical care, highlighting recent advances with potential to impact ESCC prevention, diagnosis and management. We further provide an overview of recent translational investigations contributing to our understanding of the molecular mechanisms underlying ESCC development, progression and therapy response, including insights gained from genetic studies and various murine model systems. Finally, we discuss future perspectives in the clinical and translational realms, along with remaining hurdles that must be overcome to eradicate ESCC.